2023
DOI: 10.1101/2023.10.31.564722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved detection of methylation in ancient DNA

Susanna Sawyer,
Pere Gelabert,
Benjamin Yakir
et al.

Abstract: Reconstructing premortem DNA methylation levels in ancient DNA (aDNA) has led to breakthrough studies such as the prediction of anatomical features of the Denisovan, as well as the castration status of ancient horses. These studies relied on computationally inferring methylation levels from damage signals in naturally deaminated cytosines. Because of statistical constraints, this inference requires high-coverage sequencing, and is thus not only expensive but also restricted to samples with exceptional DNA pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Meanwhile, using alternative experimental strategies could also be an option for paleomethylomics. For instance, Sawyer et al (2023) recently reported that bisulfite treatment of aDNA coupled with a single-stranded library preparation protocol could produce similar or even more accurate CpG methylation estimates as that inferred indirectly from postmortem damage, using much lower amounts of sequencing data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, using alternative experimental strategies could also be an option for paleomethylomics. For instance, Sawyer et al (2023) recently reported that bisulfite treatment of aDNA coupled with a single-stranded library preparation protocol could produce similar or even more accurate CpG methylation estimates as that inferred indirectly from postmortem damage, using much lower amounts of sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that cytosine methylation sites can survive in ancient DNA. Several studies have used standard protocols for methylation profiling, such as bisulfite sequencing and immunoprecipitation, on ancient DNA (Llamas et al., 2012 ; Sawyer et al., 2023 ; Seguin‐Orlando et al., 2015 ; Smith et al., 2015 ). Meanwhile, methylation information can be indirectly inferred from sequencing data from ancient DNA molecules treated with the UDG (uracil‐DNA glycosylase) enzyme.…”
Section: Introductionmentioning
confidence: 99%